2011
DOI: 10.1021/jf200354y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Dissolution and Antioxidant Activity of Kaempferol Using a Nanoparticle Engineering Process

Abstract: Kaempferol (KAE) is a strong antioxidant flavonoid compound, but its clinical application is limited by quantity and poor dissolution property. However, the dissolution mechanism of a kaempferol nanoparticle formulation (KAEN) has not yet been elucidated. The aim of the present study was therefore to use a nanoparticle engineering process to resolve the dissolution problem. Our data indicated that KAEN effectively increased the dissolution percentage by particle size reduction, high encapsulation efficiency, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 44 publications
3
42
0
1
Order By: Relevance
“…64 The disappearance of the RSV melting peak in the DSC thermograms of RSV-loaded NPs ( Figure 6C) indicates the absence of the drug crystalline state, suggesting that entrapped RSV is in an amorphous state of a solid molecular dispersion into the polymer matrix. 65 Furthermore, in the thermogram of RSV-loaded PLGA NPs, the endothermic peak of PLGA appeared at about 375°C, as observed in the pure PLGA. The scans of PLGA-CS3 and PLGA-Alg3 NPs, chosen as examples, exhibited a considerable shifting of the endothermic decomposition peak of PLGA from about 375° to 317° and 327°C, respectively.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 77%
“…64 The disappearance of the RSV melting peak in the DSC thermograms of RSV-loaded NPs ( Figure 6C) indicates the absence of the drug crystalline state, suggesting that entrapped RSV is in an amorphous state of a solid molecular dispersion into the polymer matrix. 65 Furthermore, in the thermogram of RSV-loaded PLGA NPs, the endothermic peak of PLGA appeared at about 375°C, as observed in the pure PLGA. The scans of PLGA-CS3 and PLGA-Alg3 NPs, chosen as examples, exhibited a considerable shifting of the endothermic decomposition peak of PLGA from about 375° to 317° and 327°C, respectively.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 77%
“…225 Nanosized kaempferol enhances the antioxidant activity of kaempferol. 226 Nanokaempferol developed using a layer-bi-layer technique with a size range of 149-161 nm enhances the bioavailability of kaempferol in bone marrow. 227 Oral bioavailability of kaempferol is enhanced using self-nanoemulsifying drug delivery system and nanoniosome delivery techniques with a size range of 34-141 nm in dog and rat models.…”
Section: Nanokaempferolmentioning
confidence: 99%
“…Some studies have also demonstrated that EE-PVA effectively changed the crystalline structure of hydrophobic compounds such as quercetin, 28 kaempferol, 35 and silybinin. 36 In addition, we further investigated the intermolecular interactions of EE-PVA polymer with 734THIF using FTIR spectrometry and 1 H-NMR spectroscopy. FTIR spectra of raw 734THIF, 734N, and blank-N are shown in Figure 5A.…”
mentioning
confidence: 99%